Experiências de internacionalização e aprendizagem para comunicação intercultural - Nogueira, Ariane Harbekon [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The objective of this study is to discuss the importance of internationalization in higher education by providing intercultural experiences that constitute an active methodological practice to support the training of future professionals who will work in a multicultural society. For this, we had as methodology tools the bibliographical research, to gather theoretical references on the theme of globalization and multiculturalism, interculturality, intercultural communication and internationalization; documentary research on the specific official documents of Unesp that deal with the internationalization policies of the University; semi-structured interview by Google Forms questionnaire applied to Brazilian and foreign students, professors and researchers from FAAC / Unesp so that we can know their internationalization experiences. As main results, we obtained very positive visions regarding the internationalization experiences of teaching, proving their contribution to the promotion of intercultural communication.

O presente trabalho tem como objetivo discutir a importância da internacionalização no âmbito do ensino superior ao proporcionar experiências interculturais que se configuram como práticas metodológicas ativas de apoio à formação de futuros profissionais que atuarão em uma sociedade multicultural. Para tal, tivemos como instrumentos metodológicos a pesquisa bibliográfica, para reunir referenciais teóricos sobre a temática da globalização e multiculturalismo, interculturalidade, comunicação intercultural e internacionalização; pesquisa documental sobre os documentos oficiais específicos da Unesp que tratam sobre as políticas de internacionalização da Universidade; entrevista semi-estruturada via questionário do Google Forms aplicado a estudantes brasileiros e estrangeiros, docentes e pesquisadores da FAAC/Unesp a fim de que possamos conhecer suas experiências de internacionalização. Como principais resultados, obtivemos visões muito positivas a respeito das experiências de internacionalização de ensino, comprovando sua contribuição para o fomento da comunicação intercultural.
Keywords: Comunicação intercultural; Intercâmbio educacional; Ensino superior; Multiculturalismo; Exchange